Etos Religius dalam Tradisi Sesajen Perspektif Islam Kejawen di Jati Ombo - Hermanda, Anilla Febriaty; Sari, Mawar Puspita (Postgraduate Studies UIN Sunan Ampel Surabaya, 2023)
This study examines the practice of sesajen (ritual offerings) within the Islamic Javanese (Islam Kejawen) community of Jati Ombo Village, a tradition often perceived as contradictory to normative Islamic teachings. While sesajen is commonly regarded as an offering to spirits, in the context of Islam Kejawen it represents a spiritual expression of devotion to God. The research focuses on the transformation of sesajen from its Hindu–Buddhist origins into an Islamic form embedded in Javanese religious culture. The novelty of this study lies in its analysis of the relationship between the practice of sesajen and the theological reinterpretation undertaken by Islam Kejawen adherents, demonstrating a symbolic transformation that maintains the essence of tawhid (monotheism). Using a qualitative approach with a case study method, the research investigates ritual practices in Jati Ombo, particularly those involving bantengan art as an integral part of sesajen ceremonies. The findings reveal that within Islam Kejawen, sesajen is not viewed as spirit worship but as an expression of gratitude and a symbolic medium to strengthen spiritual connection with God Almighty. This study concludes that Islam Kejawen embodies a shift from mystical offerings toward religious offerings rooted in local Islamic spirituality.